2019
DOI: 10.1177/1470785319859210
|View full text |Cite
|
Sign up to set email alerts
|

Netnography as a marketing research tool in the fashion industry in Southeast Europe

Abstract: In the past decades, marketing has been revolutionized by digital sources, which provide marketers with rich information on potential consumers. Consequently, this article explores the evolving opportunities that online communities present to marketers in collecting consumer insights. It advances Southeast Europe’s marketing researchers’ understanding of netnography by introducing them to its concept, procedures, and implications. This study triangulates the data through utilizing seven one-to-one in-depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…These capabilities and characteristics of netnography support the rationale behind the prescription of the methodology instead of the popular decision tree and other extensively used techniques that are not enjoying similar benefits in insights and richness of data. Few of the recent influential publications that have entrusted and discussed the netnography technique as a tool to yield customer insights are Eaton and Pasquini (2020); Tavakoli and Wijesinghe (2019); Wang (2019a); Wang (2019b); Xharavina et al (2019); Lund et al (2019); Toledano (2017); Thanh and Kirova (2018); and Weijo et al (2014).…”
Section: Qualitative Consumer Research and Netnographymentioning
confidence: 99%
“…These capabilities and characteristics of netnography support the rationale behind the prescription of the methodology instead of the popular decision tree and other extensively used techniques that are not enjoying similar benefits in insights and richness of data. Few of the recent influential publications that have entrusted and discussed the netnography technique as a tool to yield customer insights are Eaton and Pasquini (2020); Tavakoli and Wijesinghe (2019); Wang (2019a); Wang (2019b); Xharavina et al (2019); Lund et al (2019); Toledano (2017); Thanh and Kirova (2018); and Weijo et al (2014).…”
Section: Qualitative Consumer Research and Netnographymentioning
confidence: 99%
“…Additionally, this study utilized netnographyan online qualitative research method that studies consumer interactions and behaviours in online communities (Kozinets, 2002;Xharavina et al, 2020). It is a suitable approach for sensitive research topics, like metrosexuality in SEE (Costello, 2017).…”
Section: Netnographymentioning
confidence: 99%
“…This is why brands must engage in meaningful conversations in order to build a strong association with their users. Kapoulas et al used Netnography as a tool to study the Fashion industry in the South East which concluded that brands which follow a proper schedule of uploading their content online were more likely to generate sales (Kapoulas et al, 2020). Dwivedi et al recognise three types of Facebook groups: Associative, Aspirational and Advertising and concluded that associative groups have the most credible exchange of communication between the brand and the community (Dwivedi et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%